SATELLITE NAVIGATION SYSTEM MARKETING (Economics and region, 2017)
UDC 69.003:658.8 Chychkalo-Kondratska, D.Sc. (Economics),Professor.      V. Dobryanskaya,       PhD       (Technical),Associate Professor. V. Miroshnichenko, Senior Lecturer. Poltava National Technical Yurii Kondratyuk University. Satellite navigation system marketing. Satellite navigation system was developed as a defense project, but in recent decades, has formed a global market of users of satellite navigation systems, and manufacturers of navigational equipment. The article is devoted to analysis of market prospects by the European satellite navigation system Galileo. Conducted SWOT-analysis, allowed to conclude that the project «Galileo» has advantages and problems.The main problem is the complexity of creating a satellite constellation, because Europe does not have its own reliable and cheap launch vehicles. The solution may be the inclusion in the draft of Ukraine, who has processed technology of rocketry. Keywords: marketing, the global market, investment project, satellite navigation systems, launch vehicles, SWOT-analysis, marketing of the project.